Myconanotechnology and application of nanoparticles in biology - Gupta, Shraddha; Sharma, Kavita; Sharma, Ravi (Recent Research in Science and Technology, 2012)
To develop a new green approach for biosynthesis of nanoparticles, myconanotechnology has been represented as a novel field of study in nanotechnology. Several scientists have re-explored the fungi including yeasts and filamentous fungi as a biofactory for eco-friendly, cost-effective synthesis of nanoparticles. The advantageous of fungal-mediated biosynthesis of nanoparticles have turned the attention of scientists to the kingdom of fungi. The most notable benefits of applying fungi in nanoscience are their resistance to many harsh conditions as well as secretion of extracellular reductive proteins so that it makes the downstream processes easier. This review focuses on general introduction, synthesis of nanoparticles through fungi and its application in biology.